2020
DOI: 10.1002/ijfe.2012
|View full text |Cite
|
Sign up to set email alerts
|

The DuPont financial indicators and the short‐term market performance of Chinese cross‐border M&As: The moderating role of payment method

Abstract: Using the data of Chinese cross‐border mergers and acquisitions (M&As) from 2003 to 2017, we investigate the influence of the internal financial conditions of enterprises on the short‐term market performance of Chinese cross‐border M&As by applying improved DuPont financial analysis, an event study and regression analysis and further explore the moderating effect of payment method in Chinese cross‐border M&A. The findings are threefold. First, we observe significant positive cumulative abnormal returns (CARs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…Furthermore, to prevent the outflow of critical technologies, governments restricted foreign acquisitions in certain high-tech sectors 37 . Additionally, some countries had rigorous review and approval processes for cross-border M&A, potentially involving multiple governmental departments and taking considerable time to finalize, which resulted in delays or even failures of M&A transactions 38 .…”
Section: Theoretical Basis Analysis and Research Hypothesismentioning
confidence: 99%
“…Furthermore, to prevent the outflow of critical technologies, governments restricted foreign acquisitions in certain high-tech sectors 37 . Additionally, some countries had rigorous review and approval processes for cross-border M&A, potentially involving multiple governmental departments and taking considerable time to finalize, which resulted in delays or even failures of M&A transactions 38 .…”
Section: Theoretical Basis Analysis and Research Hypothesismentioning
confidence: 99%
“…Regarding methodology, studies about the impact of M&A on target firms can be categorized by types of measurement as follows: financial and non-financial analysis. Some common financial analyzing methods are stock-market-based analysis (Lin et al , 2020) and accounting-based analysis (Healy et al , 1992; Feng and Xie, 2020). Advantages of financial methods are objective results, the ease at quantifying results, comparability of results over time and the ability of self-computation.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Furthermore, in recent years, some researchers have indicated that there should be cross-border M&As [9]. The corresponding literature has focused on the antitrust review of cross-border M&As.…”
Section: Introductionmentioning
confidence: 99%